Transepithelial transport and structural changes of chicken angiotensin I-converting enzyme (ACE) inhibitory peptides through Caco-2 cell monolayers. (June 2018) - Sangsawad, Papungkorn; Choowongkomon, Kiattawee; Kitts, David D.; Chen, Xiu-Min; Li-Chan, Eunice C.Y.; Yongsawatdigul, Jirawat
Graphical abstract: Highlights: Potency of ACE inhibition depends on the extent of intact peptide permeability. KPLL showed the highest cell permeability as compared to KPLLCS and ELFTT. KPLL was hydrolyzed to KP and LL and all were transported through Caco-2 cells. The KP at N-terminus of KPLL are key residues for ACE inhibition. Abstract: Permeability of angiotensin I-converting enzyme (ACE) inhibitory peptides (KPLLCS, ELFTT, and KPLL) identified from the in vitro gastrointestinal digest of cooked chicken breast was investigated using the Caco-2 cell model system. KPLLCS was originally the most effective ACE inhibitor (IC50 0.37 μM), but it was degraded during permeation through Caco-2 cells. Among these peptides, KPLL showed the highest permeability in intact form, and partially degraded to KP and LL, which still showed ACE inhibitory activity after permeation. ACE inhibitory activity of permeated KPLL was highest of 56%. KPLL and KP possessed a mixed inhibitor characteristic, while LL was a non-competitive inhibitor. Based on molecular docking, K at N-terminus of KPLL is a key structure contributing to ACE inhibition as it can occupy the active site of ACE. Determining the structural stability and degree of peptide transport across epithelial cell is required to confirm their potential as ACE inhibitors.